Pengaruh Transformational Leadership, Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja Guru PKBM XYZ dari Sudut Pandang Kristen - Natan, Azerina Priskila; Hidayat, Dylmoon (Universitas Kristen Satya Wacana, 2023)
A teacher's performance can influence the quality of student learning at school. This is because teachers have an important role in the world of education. His words and behavior will be an example for the students he teaches. Students can feel that teachers do not give their best in preparing learning materials, complain easily, or are unable to work together with leaders. There are many factors that can influence teacher performance, namely type of leadership, job satisfaction, and work motivation. Research was conducted to determine whether there is a positive influence between transformational leadership, job satisfaction, and work motivation on teacher performance at PKBM XYZ. This research is quantitative research with 35 respondents using path analysis. The results of this research indicate that (1) transformational leadership has a positive effect on teacher performance, (2) there is little evidence that job satisfaction has a positive effect on teacher performance, (3) work motivation has a positive effect on teacher performance. The teacher performance variable can be explained by the variables transformational leadership, job satisfaction and work motivation by 21%.